Inactivation of biofilm-bound bacterial cells using irradiation across UVC wavelengths. (15th June 2022) - Ma, Ben; Seyedi, Saba; Wells, Emma; McCarthy, David; Crosbie, Nicholas; Linden, Karl G.
Highlights: UV disinfection of biofilm-bound bacteria was investigated. 5 UV sources were tested emitting at wavelengths from 222 to 282 nm. UV transmittance and absorbance across the biofilm structure was documented. UV LEDs emitting at 270 nm provided the best disinfection performance. Inactivation of biofilm-bound cells was much lower than planktonic cells. Abstract: Opportunistic pathogens (OPs), such as Pseudomonas spp., Legionella spp., and mycobacteria, have been detected in biofilms in drinking water distribution systems and water storage tanks and pose potential risks to finished drinking water quality and safety. Emerging UV technologies, such as UV light emitting diodes (LEDs) and krypton chloride (KrCl*) excimers, could provide an alternative to chemical-based secondary disinfection (i.e., chlorine or chloramines) for controlling biofilm-bound OPs. UV systems offer long lifetimes, ability to select wavelength, small size with high power density, and limited-to-no disinfection by-product formation. In this study, inactivation of biofilm-bound Pseudomonas aeruginosa cells across different maturities was investigated using five UVC devices with different peak emission wavelengths, including a KrCl* excimer (222 nm), a low pressure mercury vapor lamp (254 nm), and three UV LEDs (260 nm, 270 nm, and 282 nm). The UV transmittance and absorbance through the biofilm structure was also documented for the first time using a unique approach. Our results show all UVC devices can inactivate biofilm-bound P. aeruginosa cells up to a point, among which the UV LED with peak emission at 270 nm provided the best disinfection performance. UV sensitivities of biofilm-bound cells decreased with biofilm maturity and while initial rates of inactivation were high, no more than 1.5-2.5 log reduction was possible. Re-suspended biofilm bacteria in aqueous solution were highly sensitive to UV, reaching greater than 6 log reduction. UV shielding by biofilm constituents was observed and was likely one of the reasons for UV resistance but did not fully explain the difference in UV sensitivity between biofilm-bound cells versus planktonic cells. This study improves upon fundamental knowledge and provides guidance for innovative designs using emerging UV technologies for biofilm and pathogen control in water distribution systems. Graphic abstract: Image, graphical abstract